Treated Domestic Sewage as A Nutrient Source for Tomatoes (Solanum Lycopersicum) Growth and Yield in A Hydroponic System in Yaoundé – Cameroon - Chimi, Adrienne Njomou; Lekeufack, Martin; Djumyom, Guy Valerie Wafo; Nguetsop, Victor François; Fonkou, Theophile (European Journal of Applied Sciences, 2024)
The exploitation of marshy lowlands for agricultural purposes in African cities, with a clear predominance of market gardening, calls for concern about the availability of exploitation sites and the doubtful quality of the water used. This situation, particularly in urban areas, prompts farmers to look for alternative solutions, like hydroponics, a growing technique that does not only rationalizes the use of space, but saves water and mineral fertilizers, and simplifies growing techniques, but above all eliminates soil-related problems and increases yields. The aim of this research is to use treated sewage in hydroponics for tomato production in urban agriculture in the city of Yaoundé. The experiments were conducted in a completely randomized bloc design system with three replications. The effluents were obtained from the Messa domestic sewage treatment plant. Five treatments including raw effluent (T1); 50% diluted effluent (T2); 75% diluted effluent (T3); Maxigro 10-5-14 chemical fertilizer solution at a dose of 100 g per 50 l of tap water (positive control) (T4), and tap water (negative control) (T5) were applied to the tomatoes. The growth parameters considered plant height, leave number, and number of fruits. Lycopene, protein, phenol, and flavonoid content were also evaluated. The results show that 75% diluted effluent (T3) significantly (P<0.05) improved tomato growth, with values of 24±0.60 cm for plant height, 24.16±0.074 for leave number, and 72±6 for number of fruits compared with the negative control. However, the raw effluent (T1) and the 50% diluted effluent (T2), significantly improved the organo-mineral quality of the tomatoes (P<0.05) with 2.05±0.50 µg/g and 1.74±0.11 µg/g for lycopenes, 0.14 ±0.04µg/100g and 0.21±0.011 µg/100g for proteins, 5.73±0.25 µg/100g and 6.32±0.35 µg/100g for phenols, and 21.41±3.09 µg/100g and 29.08 ±2.27µg/100g for flavonoids respectively) compared to the negative control. The highest yield was obtained with the positive control (T4), followed by treatment (T3); with estimated fruit number of 34±3 and 27±2 fruits/m2 respectively. The reuse of treated wastewater in hydroponics would be an innovative technique that would alleviate the current problems of urban agriculture in the city of Yaoundé.